The influence of sleep on job satisfaction: examining a serial mediation model of psychological capital and burnout - Opoku, Mavis Agyemang; Kang, Seung-Wan; Choi, Suk Bong (Frontiers in Public Health, 2023)
Introduction This study draws on the conservation of resources theory to investigate whether the loss of sleep can trigger the loss of additional resources that are necessary for work. Methods Using cross-sectional design of 322 call center employees working at a government-owned public bank in South Korea, we test the study hypotheses using regression and bootstrapping indirect effects analyses. Results The results of analyses show that insufficient sleep increases employee burnout and that psychological capital mediates this relationship. We also find that insufficient sleep decreases job satisfaction via a serial mediation model such that insufficient sleep reduces psychological capital, which in turn increases burnout, and ultimately results in lower job satisfaction. Discussion The findings reinforce the previous assessment that although sleep is a non-work factor, its impact spills over to the workplace. Theoretically, this study goes beyond direct effect to uncover the underlying or mediating mechanisms that account for the impact of the sleep-burnout relationship and the sleep-job satisfaction relationship. For managers, the results highlight the significance of sleep to employees’ overall health and well-being and thus underscore the need to foster a work culture that recognizes and prioritizes employee sleep needs.